Power and Knowledge: Analysis of LGBTIQ Discourse in Sociology of Religion Based on Queer Theory - Lidya Kandowangko (Institut Agama Islam Negeri (IAIN) Manado, 2023)
This article intends to analyze the LGBTIQ discourse in sociology of religion based on queer theory. The conceptual framework in conceptualizing research results refers to the terminology of Michael Foucault's thoughts regarding the practice of discourse and power, and the queer theory approach. This research was conducted using a qualitative research method based on a critical discourse analysis approach. The critical discourse analysis approach is used in order to gain scientific knowledge and understanding regarding the reproduction of LGBTIQ discourse influenced by socio-religious values as part of sociology of religion studies. The findings of this study are that the power and knowledge gained from the terminology of Michael Foucault determined the paradox of discourse. Especially when it is associated with a socio-religious scientific background, it also creates contradictions that affect the socio-religious practices of the community in accepting the existence of LGBTIQ as an individual and community identity. However, as a sociology of religion researcher, we can use or integrate queer theory to produce inclusive knowledge because of the data collected based on LGBTIQ experiences, So that the scientific study in sociology of religion related to LGBTIQ research is more valid and reliable and does not tend to discriminate against their existence as part of humanity.